Quatro décadas de grandes expansões planejadas na capital paraibana (1913-1953). - Ressa, Patricia Gigliola de Queiroga (2012)
This work shows (a) how the urban extensions covering 50 or more hectares contributed to the physical growth of João Pessoa, the capital of Paraíba, Brazil, between 1913 and 1953, and (b) that they generated most of the urban and suburban fabric that was added to the town in that period of time. It analyzes in depth these additions, treating aspects such as features of the site, layout characteristics and integration between the layout and the nearby tissues. Such a study had not been conducted yet and is essential for the local urban history. The theoretical basis of the dissertation is the analysis of over twenty large extensions planned in Europe and the Americas which it presents. The method adopted for the carrying out of the most relevant part of the study of the additions was the morphological analysis of their layout. Seven extensions added 770 hectares to the town between 1913 and 1953, which is over 50% of its overall extension in that period. Curiously the two extension plans which were not implemented were just those designed by two famous Brazilian town-planners: Saturnino de Brito and Nestor de Figueiredo.